Prenylated and geranylated flavonoids increase production of reactive oxygen species in mouse macrophages but inhibit the inflammatory response - Hošek, Jan; Toniolo, Alice; Neuwirth, Ondřej; Bolego, Chiara (Journal of natural products, 2013)
In this study, four prenylated and geranylated flavonoids, cudraflavone B (1), pomiferin (2), osajin (3), and diplacone (4), were tested for their antioxidant and anti-inflammatory effects and to identify any potential relationships between chemical structure and antioxidant or anti-inflammatory properties. The selected flavonoids were examined in cell-free models to prove their ability to scavenge superoxide radicals, hydrogen peroxide, and hypochlorous acid. Further, the ability of the flavonoids to influence the formation of reactive oxygen species in the murine macrophage cell line J774.A1 was tested in the presence and absence of lipopolysaccharide (LPS). The ability of flavonoids to inhibit LPS-induced IκB-α degradation and COX-2 expression was used as a model for the inflammatory response. The present results indicated that the antioxidant activity was dependent on the chemical structure, where the catechol moiety is especially crucial for this effect. The most potent antioxidant activities in cell-free models were observed for diplacone (4), whereas cudraflavone B (1) and osajin (3) showed a pro-oxidant effect in J774.A1 cells. All flavonoids tested were able to inhibit IκB-α degradation, but only diplacone (4) also down-regulated COX-2 expression.
Keywords: flavonoidy; Flavonoids; isoflavony; Cyclooxygenase 2; makrofágy; Animals; oxid dusnatý; Nitric Oxide; Mice; lipopolysacharidy; antioxidancia; Anti-Inflammatory Agents; prenylace; Prenylation; Macrophages; Cyclooxygenase Inhibitors; antiflogistika; Antioxidants; Benzopyrans; kinasa I-kappa B; Isoflavones; cyklooxygenasa 2; zvířata; benzopyrany; I-kappa B Kinase; Lipopolysaccharides; inhibitory cyklooxygenasy; myši